Islamic Peril - Laurent Bonnefoy (International Institute of Islamic Thought, 2004)
At the junction of history, international relations, political science, and communication studies, Karim H. Karim’s Islamic Peril provides serious and in-depth research on the media coverage of violence involving Muslim individuals and groups. This updated edition of the book, first published in 2000, adds a preface and an afterword that briefly account for 9/11 and its aftermath. While studying the construction of Islam as the primary “Other” in Canada’s main print media since the beginning of the 1980s, the author argues that the numerous (mis)representations and stereotypes of Muslims are based on a lack of religious, sociological, political, and historical knowledge rather than on what Karim calls a “centrally organized journalistic conspiracy against Islam” (p. 4). The author concentrates on the construction, flow, and reproduction of globally dominant interpretations through relations of power and domination between the North and the South, but also inside the North’s media. His focus on journalism’s internal mechanisms (e.g., dependence on a limited number of sources, the need for simplification, and the clash of interests between information and business) and the wider sociopolitical domination processes (e.g., the end of the cold war or unipolarity) prevents the analysis from being overtly simplistic and adopting a victim mentality. The author does not just highlight the (mis)representations; he also tries to analyze them. His approach is optimistic, for it implies there is no fatality in reproducing stigmatization and stereotypes. Karim studies what could be called the “Islamization of representations”: the social construction of the linkage between facts of violence that are historically and sociologically rooted and the notion of Islam as an essence. His analysis does not revolutionise the approach toward discourses on Islam, for one can feel how much he was influenced by the ...